Features neuro-endocrine support diversity of immune responses to chronic stress in male rats - Zajats, Lyubomyr M; Polovynko Іlona S; Zukow, Walery (Journal of Education, Health and Sport, 2017)
Background. In the previous report, we showed that the immune response to chronic stress in male rats are characterized by diversity.We assume that a variety of immune responses to chronic stress caused by a variety of reactions neuroendocrine factors.The aim of this study is to test the hypothesis. Material and methods. The experiment is at 50 white male rats. Of these 10 animals not subjected to any influences and 40 within 7 days subjected to moderate stress by daily 30-minute immobilization. The day after the completion of stressing neuro-endocrine and immune parameters were determined. Results. Found that each immune cluster is characterized by particular constellation of neuroendocrine factors. Interestingly, the most numerous and tangible change occurred in rats with minimal deviations immune status. Moderateinhibitionmicrophage, killerandT-cellularlinksincombinationwithastrongactivationmacrophagelink in another cluster is associated with similarly the previous cluster increase the thickness of the reticular and fascicular zones adrenal cortex, but without increasing plasma levels of testosterone and corticosterone, combined with a decrease in the thickness of the glomerular zone and mineralocorticoid activity. More pronounced poststressory changes immune system, first activation of macrophage link in combination with inhibition of microphage and T-link associated with the most elevated sympathetic tone and low vagal tone as well as moderately elevated level of corticosterone, combined with moderately low level of triiodothyronine.Conclusion. Variety of immune responses to chronic stress caused by a variety of reactions immunomodulating neuroendocrine factors.